2013
DOI: 10.1371/journal.pone.0069810
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of GmHsp90s, a Heat Shock Protein 90 (Hsp90) Gene Family Cloning from Soybean, Decrease Damage of Abiotic Stresses in Arabidopsis thaliana

Abstract: Hsp90 is one of the most conserved and abundant molecular chaperones and is an essential component of the protective stress response; however, its roles in abiotic stress responses in soybean (Glycine max) remain obscure. Here, 12 GmHsp90 genes from soybean were identified and found to be expressed and to function differentially under abiotic stresses. The 12 GmHsp90 genes were isolated and named GmHsp90A1–GmHsp90A6, GmHsp90B1, GmHsp90B2, GmHsp90C1.1, GmHsp90C1.2, GmHsp90C2.1 and GmHsp90C2.2 based on their cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 60 publications
3
60
0
Order By: Relevance
“…HSP90 can bind to Argonaute (AGO1) and facilitate the assembly of plant RNA‐induced silencing complexes (Iki et al , ). Although several groups have suggested the involvement of HSP90 in plant drought stress response in different species (Song et al , ; Xu et al , ), the underlying regulating mechanism and downstream components remain elusive. In this study, we demonstrated that MeHSP90.9 interacts with MeWRKY20 and MeCatalase1 in nuclei and peroxisome in tobacco leaves, respectively (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…HSP90 can bind to Argonaute (AGO1) and facilitate the assembly of plant RNA‐induced silencing complexes (Iki et al , ). Although several groups have suggested the involvement of HSP90 in plant drought stress response in different species (Song et al , ; Xu et al , ), the underlying regulating mechanism and downstream components remain elusive. In this study, we demonstrated that MeHSP90.9 interacts with MeWRKY20 and MeCatalase1 in nuclei and peroxisome in tobacco leaves, respectively (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The other HSP20 families were up regulated in both cultivars, but were not passed cut-off in Daewon. Some of HSP90 genes include GmHsp90A1 (Glyma.09g131500) and GMHsp90C1.2 (Glyma.02g124500) were reported as rapidly accumulate and be maintained for a long period (Xu et al 2013). These genes were found in up-regulation genes of Hwangkeum, but did not found to be DEGs in Daewon.…”
Section: Discussionmentioning
confidence: 99%
“…The cDNA was performed on Rotor-gene Q real-time PCR system with SYBR Green PCR Kit (Qiagen, Germantown, MD, USA) and transcript specific primers. The cDNAs have been checked expression of heat stress marker (GMHsp90C2.1) which can validate for the plants applied heat stress (Xu et al 2013 …”
Section: Validation Of Differentially Expressed Genes From Rna-seq Usmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanism of chamomile's resilience to natural conditions is not well-understood. Several reports have indicated that Hsp90 is closely related to the stress resistance of plants (Xu et al, 2013). Whether there is functional connection between Hsp90 and the stress resistance in M. recutita remains unknown.…”
Section: Introductionmentioning
confidence: 99%